11 LEADERSHIP PRINCIPLES OF INDONESIAN NATIONAL ARMED FORCES IN NATURAL DISASTER MANAGEMENT - Yusuf Ali; Aris Sarjito; Susanto Susanto (Journal of Leadership in Organizations, 2021)
Introduction: Natural disasters is one of the real threats which cause the loss of life, property, and refugees. Background Problems: The role of the Indonesian National Armed Forces (TNI) in natural disaster management becomes an interesting thing to study when natural disasters occur in Indonesia. Novelty: This article reveals the analysis result of the implementation of TNI’s principles in disaster management, especially in the following regions: Palu, Sigi and Donggala (Pasigala), Central Sulawesi Province. Research Methods: The research was conducted using qualitative research methods. The collected data was analyzed using qualitative data analysis techniques. Finding/Results: Based on the results of the study, it was concluded that the role of TNI’s leadership style was very prominent to fill the vacancies of Regional Leaders in certain areas experiencing disaster. The support of TNI personnel in natural disaster management cannot be separated from the implementation of 11 TNI leadership principles, which consist of: Takwa, Ing Ngarsa Sung Tulada, Ing Madya Mangun Karsa, Tut Wuri Handayani, Waspada Purba Wisesa, Ambeg Parama Arta, Prasaja, Satya, Gemi Nastiti, Belaka, and Legawa. The application of these principles can be seen in emergency response situations, where TNI plays an important role, in which their instructions were conformed by the community. In disaster mitigations, they evacuated victims, rebuilt worship places, looked around for logistical sources for the community, were incharged for possible criminal actions, such as eradicated looting acts, arrested the perpetrators and handed them to the local Police. Thus, it can be said that the leadership of TNI has succeeded in handling natural disasters in Pasigala, Central Sulawesi. It can be then recommended that the Indonesian Government and stakeholders should improve the quality of training and education for leadership and disaster management by implementing the leadership principles of TNI, as well as synergizing with TNI in disaster management